The Sleep Quality of Breast Cancer Patients - devita alifiyanti; Yanti Hermayanti; Dyah Setyorini (Journal of Nursing Care, 2018)
The quality of sleep is required by breast cancer patients to regenerate and repair the body cells. When patients’ sleep is disturbed, it may be affected to the physiological conditions, such as decreased appetite, weight loss, anxiety, irritability, and changes in natural and cellular immune functions. Breast cancer therapies can affect the quality of sleep. This study aimed to determine the sleep quality of breast cancer patients that had treatments in a public hospital in Bandung. This research used the quantitative descriptive approach. The sample was selected using the consecutive sampling technique (n = 31). Data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Sleep quality was categorized as good when the total score was ≤ 5, and sleep quality was poor when the total score was > 5. The results of this study indicated that all respondents (100%) had poor sleep quality. The components that contributed to the assessment were sleep latency, sleep duration, sleep efficiency, and daytime dysfunction. The worst sleep quality with the highest score (18) occurred in respondents who had radiotherapy and mastectomy (2 persons), and respondents in advanced stage (3 persons). This study concludes that the pharmacological therapies and the stages of cancer contributed to the sleep quality of breast cancer patients. It is expected that health professionals and hospitals notice the patient’s sleeping needs during treatment at the hospital.